Munshi Abdullah : an early critic of Malay language, culture and society - Hashim, Rosnani (The Other Press, 2010)
None has observed the Malay language,culture and society of the nineteenth century as avid and critical as Munshi Abdullah or Abdullah Abdul Kadir. He has been regarded as the father of modern Malay literature because of his new style of writing and its focus which departed from the old style of Malay literature. In fact, he can also be regarded as the father of Malay ethnography and social critic for he provided a vivid description and critical analysis of the Malay culture and society of the period. He was genuine language teacher for the whole of his life beside being a critic of his people with regard to knowledge and education.